Socializing The Use Of Tokowa For Buying Umkm Products At Teman Studio Creative - Ayu, Wanda Afrilia; Bagaskara, Alvian Ananta; Cahyanto, Triawan Adi (Universitas Muhammadiyah Jember, 2024)
This community service initiative aims to assist individuals in enhancing their digital platform proficiency, particularly about Tokowa, for their UMKM products. The program will incorporate various approaches, such as lectures, software demonstrations, feedback queries, and discussions to evaluate user feedback. Participants will depart with a better grasp of Tokowa and an improved digital skill set. The program's outcome demonstrates that participants have expanded their knowledge of Tokowa, and user feedback illustrates a positive experience with the platform's functionality and user-friendliness. The system's documentation, including displays and graphs of functionality test results, will enable participants to see the advantages of using Tokowa. By engaging in this activity, individuals can enhance their digital skills and acquire valuable knowledge about Tokowa, which can help them expand their UMKM businesses